Negotiation of Javanese Cultural Identity into Arabic Culture in the Myth Film Translation of ‘Lima Wasto’ - Mukminin, Muhamad Saiful; Muhhit, Ahmad Abdul; Alfath, Muhammad Habibie; Ahmed, Aqeel; Khandoker, Md. Kamruzzaman (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2025)
This study aims to identify the patterns and factors of Javanese cultural identity negotiation in the Arabic translation of the film Lima Wasto. The research data consists of subtitles from both the original Javanese version and the Arabic translation available on the VIU platform. A qualitative approach is employed using descriptive-comparative and interpretative methods. Data collection is conducted through observation and note-taking techniques. Data analysis follows the interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal four patterns of cultural negotiation: material culture, social culture, gestures and habits, and ecology. Cultural negotiation occurs due to differences in value systems, symbolism, and social structures between Javanese and Arab cultures. The main factors driving negotiation include the purpose of translation, symbolic differences, the norms of the target culture, and limitations of audiovisual media. Domestication strategies are often applied to make the meaning acceptable in the target culture. In conclusion, negotiation is an inevitable form of compromise in intercultural and interlingual translation.